Lesson hub

Can't find the answer? Try online tutoring

How it Works

We have the UK’s best selection of online tutors, when and for how long you need them.

Getting 1-on-1 support is cheaper than you might think.

Participating users

Welcome to our free-to-use Q&A hub, where students post questions and get help from other students and tutors.

Follow the trail of responses and if you have anything to add please sign up or sign in.

You can ask your own question or look at similar Maths questions.

Hi Amelia,

This is a tricky question and Jonny G is correct in saying there is an error in your statement - it should be pi/2. The outline for proving this is to assume x=tan(y)

This implies that arctan(x)=y.      [I prefer arctan to tan^-1 ]

Now there is a general formula tan(y)=cot(pi/2-y).

Thus arctan(x)+arccot(x)

=arctan(tan(y))+arccot(tany)

=arctan(tan(y))+arccot(cot(pi/2-y))=y+pi/2-y=pi/2 QED

Footer Graphic